Kemampuan informasi akuntansi dan nonakuntansi pada “Si Pencabut Ruko Kosong”: Bertahan atau mundur? - Valensia Febrianti; Riesanti Edie Wijaya; Maria Eugenia Hastuti (Akuntansi dan Teknologi Informasi, 2024)
This research aims to explore the ability of accounting and nonaccounting information to support management decisions whether to stay or withdraw from the Mixue franchise. This research employs qualitative methods using the interpretivist paradigm, which prioritizing in-depth interpretation of data or findings to express the inside meaning  explicitly by paying attention to related aspects holistically. The selected informant in this study has three Mixue franchise branches. Having access to financial and nonfinancial information is crucial for owners in making the right decisions about outlet operations. Moreover, strategic and innovative thinking plays an important role in maintaining and developing the business to survive in the market.